THE STUDY OF COMMUNICATIONS EPISTEMOLOGY: KNOWLEDGE AS A WHOLE OR PART OF IT? EXPLICIT OR IMPLICIT KNOWLEDGE - Muya Syaroh Iwanda Lubis; Asrindah Nasution; Nurhayati Nurhayati; Budiman Purba (Universitas Dharmawangsa Medan, 2022)
ABSTRACT The study of the aim of science, methods of generating science, its ideas, assumptions, hypotheses, distinctions from other disciplines, and how science is applied in society are all part of philosophy of science. The debate in this paper will delve deeper into the topic of Epistemology. Epistemology is a branch of philosophy. Epistemology is a discipline of philosophy that studies the nature of knowledge especially for four (four) key aspects of knowledge such as validity, structure, limits, and sources of information, and this is included in the study of legal science. The epistemological components of legal science are discussed in This case resolution procedure is broken down into numerous parts. Explaining, interpreting, and systematizing legal materials consisting of legal concepts, regulations, and decisions to decide the law that applies to legal challenges that occur is part of the process. Case resolution does not begin with legal principles, but with difficulties that take the form of explaining a variety of facts, connections, and occurrences that conceal one or more legal problems. This article explores the Study of Communication Epistemology, which studies knowledge as a whole or as a portion, and Explicit or Implicit Knowledge, which is more particular in discussing science philosophy. Keywords: Communications Epistemology, Knowledge, Explicit Or Implicit Knowledge